A case study: submarine cable in Bangladesh - its prospects, present status, and challenges ahead - Rahman, Mohammad Ziaur; Pathan, Al-Sakib Khan (IndianJournals.com, 2010)
Bangladesh has joined the submarine cable consortium in the recent past. It had been expected that the deployment of submarine cable connectivity would eliminate the digital divide and provide different e-services with an emphasis on multi services; such as data, voice, video, health care, etc. throughout the country. This work is an assessment of the current status, challenges that we are facing, and future expectations on the use of submarine cable in Bangladesh. We first briefly describe the enormous potential of submarine cable connectivity in Bangladesh. Then, we present the existing capacity of submarine cable deployed in Bangladesh and its present scenario in terms of its use. Then it goes on to compare the current prices for the different telecommunication services with that of the satellite system. To predict the demand for various telecommunication services, such as, voice, data, Internet etc., an empirical formula has been derived considering five major parameters. Though it is well-known that the economic benefits of having a reliable telecommunication infrastructure are numerous, at present Bangladesh is lacking in the deployment of appropriate telecom infrastructure. Hence, to analyze the current status, some very basic technical and socio-economic problems of submarine cable are discussed here; also the challenges of utilizing the full potential are highlighted. This study could be helpful for other developing countries that are in the similar status like Bangladesh.